Work-life Balance and Job Satisfaction of Government Employees - Emelyn Adaron; Marlo Lacerna; Candy Elizabeth Gil Salapi (Department of Management, Faculty of Economics and Business, Brawijaya University, 2021)
The awareness of balancing the quality of life of employee through HR program such as work-life balance is getting its popularity in the HR literature. This study examined the relationship between work-life balance and job satisfaction of local government employees in one of the local government units in the Philippines. The results of the study indicate that the employees do not have sufficient knowledge on the concept of work-life balance. Most of the respondents neither agreed nor disagreed to most of the statements on work-life balance. Moreover, the employees experience satisfaction in their job. Furthermore, results show that there is a significant positive relationship between work-life balance and job satisfaction. This may indicate that if the employees feel that work does not interfere with family concerns and the latter does not affect work, they will feel more satisfied with their job. Practical implications also discussed in this paper.